RELATIONSHIP BETWEEN SERUM HOMOCYSTEINE LEVELS AND MANGANESE SUPEROXIDE DISMUTASE (MNSOD) ON RETINAL NERVE FIBER LAYER (RNFL) THICKNESS IN DIABETIC RETINOPATHY AND NON-DIABETIC RETINOPATHY PATIENTS - Delfi; Rini Nurrakhmah; Rodiah Rahmawaty Lubis (Akademi Kebidanan Nusantara 2000, 2026)
Diabetic retinopathy is a visual disorder caused by abnormalities in the retina, characterized by progressive microangiopathy resulting in damage and blockage of fine blood vessels, leading to impaired retinal nutrition. This study aims to determine the relationship between serum homocysteine and MnSOD levels on retinal nerve fiber layer (RNFL) thickness in diabetic retinopathy and non-diabetic retinopathy patients. This is an analytic observational case-control study involving 31 subjects for each group. A 3 cc venous blood sample was taken to assess serum homocysteine and MnSOD levels, then analyzed by ELISA method in the integrated laboratory of the USU Medical Faculty. The results showed a significant difference in Avg RNFL and Nasal RNFL thickness between the two groups (p = 0.015), with mean AvgRNFL thickness of 100.94 (SD = 17.04) and mean nasal RNFL thickness of 90.16 (SD = 33.68). The highest MnSOD levels were found in non-diabetic retinopathy subjects with a mean of 142.77 (SD = 101.77). No significant relationship was found between homocysteine and superior RNFL (p = 0.346), inferior RNFL (p = 0.292), temporal RNFL (p = 0.109), and nasal RNFL (p = 0.190). However, a significant association was found between homocysteine and Avg RNFL (p = 0.007). In the diabetic retinopathy case group, a significant relationship was found between Hcy and Avg RNFL (p = 0.007), where an increase in serum homocysteine levels will be followed by a decrease in Avg RNFL thickness.